ECO-SPIRITUAL BASED ON MAQA>S}ID AL-SHARI>'AH: The New Relationship of Man with the Environment - Ibrahim Siregar; Suheri Sahputra Rangkuti (AL-TAHRIR, 2023)
Theoretically, Islamic doctrines can adapt to the situation and conditions of reality. However, in Islamic history, it isn't easy to find studies about the importance of establishing a relationship with nature or the environment in which that reality stands. This research offers a paradigm that bridges the new relationship between humans and the environment. At this level, the author builds a paradigm with a multidisciplinary approach. Methodologically, maqa>s}id al-shari>'ah is used as a paradigm foundation and umbrella for human actions when responding to their environment. This study found that the maqa>s}id al-shari>'ah-based eco-spiritual paradigm is embodied in spiritual actions in the form of sacralization and ecological contemplativeness. Explicatively, sacralization and ecological contemplativeness are applied based on the principles of Islamic ethics, al-insija>m (harmony), al-iqtis}a>d (equality), al-ta'a>nu>q (interdependency), and al-tanz}i>f (cleaning).